Microbiological impact of long-term wine grape cultivation on soil organic carbon in desert ecosystems: a study on rhizosphere and bulk sandy soils - Wang, Zhiheng; Li, Wenchao; Wang, Yuejuan; Wang, Xuefei; Ma, Tingting; Liu, Yanlin; Wei, Yuqing (Frontiers in Plant Science, 2024)
The improvement of nutrients in soil is essential for using deserts and desertified ecosystems and promoting sustainable agriculture. Grapevines are suitable crops for desert soils as they can adapt to harsh environments and effectively impact soil nutrients; however, the mechanisms underlying this remain unclear. This study explored the impact of the different duration(3, 6, and 10 years) of grape cultivation on soil organic carbon, physicochemical properties, enzyme activities, microbial communities, and carbon cycle pathways in both rhizosphere and bulk soils. Partial least squares path modeling was used to further reveal how these factors contributed to soil nutrient improvement. Our findings indicate that after long-term grape cultivation six years, soil organic carbon, total nitrogen, total phosphorus, microbial biomass carbon and nitrogen, and enzyme activities has significantly increased in both rhizosphere and bulk soils but microbial diversity decreased in bulk soil. According to the microbial community assembly analysis, we found that stochastic processes, particularly homogenizing dispersal, were dominant in both soils. Bacteria are more sensitive to environmental changes than fungi. In the bulk soil, long-term grape cultivation leads to a reduction in ecological niches and an increase in salinity, resulting in a decrease in soil microbial diversity. Soil enzymes play an important role in increasing soil organic matter in bulk soil by decomposing plant litters, while fungi play an important role in increasing soil organic matter in the rhizosphere, possibly by